Lost in translation: the lack of agreement between surgeons and scientists regarding biomaterials research and innovation for treating bone defects - Laubach, Markus; Whyte, Stephen; Chan, Ho Fai; Frankenbach-Désor, Tina; Mayer-Wagner, Susanne; Hildebrand, Frank; Holzapfel, Boris M.; Kneser, Ulrich; Dulleck, Uwe; Hutmacher, Dietmar W. (BMC medicine, 2024)
With over 2 million grafts performed annually, bone ranks second only to blood in the frequency of transplants. This high demand is primarily driven by the persistent challenges posed by bone defects, particularly following trauma or surgical interventions such as tumour excision. The demand for effective and efficient treatments has increased exponentially in the twenty-first century. Limitations associated with autologous bone grafts drive exploration into replacements, including allografts, synthetic substitutes, and 3D-printed scaffolds. This research aimed to unravel disparities in the knowledge and evaluation of current and future bone defect treatments between surgeons and biomaterial scientists.